Discourse «Diplomacy and Foreign Policy in the content of media in Kazakhstan» (Herald of Journalism, 2020)
The theme of international relations and diplomacy, in the content of modern broadcasting in the Republic of Kazakhstan, as everywhere else in the world, holds a special place. In foreign bibliography actively discussed issues of journalistic ethics, standards of conduct for journalists within po- liteness. Scientists of Journalism’ Department of Al-Farabi Kazakh National University works on the topic. It seems similar discourses and publications expectable in the space of Central Asia. The material will be useful for stu- dents majoring in «International Journalism».
Keywords: Central Asia, Kazakhstan, media, Foreign Affairs, diplo- macy, TV, radio, international research.